Differences in endodontic emergency management by endodontists and general dental practitioners in COVID-19 times - Ayfer Atav ATES; Taher ALOMARI; Anuj BHARDWAJ; Abedelmalek TABNJH; Gianluca GAMBARINI
Abstract The aim of this study was to assess the differences, if any, between general dental practitioners (GDPs) and endodontists, in the diagnosis and treatment of endodontic emergencies during the worldwide outbreak of COVID-19. An online questionnaire was randomly sent by social media to clinicians in different countries from 24 April, 2020 to May 4, 2020. The survey consisted of a series of questions about demographic characteristics, endodontic emergency diagnoses, approaches to prevent aerosol formation, drug prescriptions in case of symptomatic irreversible pulpitis, and the ways in which dentists managed endodontic emergencies during the COVID-19 lockdown. A total of 1,058 dentists responded to the questionnaire; 344 (32.6%) of the participants were endodontists. Slightly less than half of the participants (n = 485, 45.8%) worked during the lockdown, but only 303 participants (28.6%) treated endodontic cases/emergencies. The responses showed agreement between endodontists and GDPs regarding the diagnosis of symptomatic irreversible pulpitis (SIP), symptomatic apical periodontitis (SAP), reversible pulpitis, and asymptomatic irreversible pulpitis (AIP). SIP and SAP were considered an emergency, whereas reversible pulpitis and AIP were not considered an emergency (p > 0.05). Non-aerosol-generating procedures and treatment approaches differed between the groups (p < 0.05). One-third of the participants did not use rubber dam (p > 0.05). Ibuprofen and amoxicillin-clavulanic acid were the most frequently prescribed drugs for pain associated with SIP. In conclusion, the most relevant findings in our survey were the differences between endodontists and GDPs in diagnosis, precheck triage, deep caries excavation procedures, and endodontic emergency pain relief strategies.